Outcome in dogs with curative‐intent treatment of localized primary pulmonary histiocytic sarcoma. (19th December 2021) - Murray, Caroline A.; Willcox, Jennifer L.; De Mello Souza, Carlos H.; Husbands, Brian; Cook, Matthew R.; Clifford, Craig; Leeper, Haley; Pellin, MacKenzie; Richardson, Danielle; Herrera, Chamisa L.; Krick, Erika; McMillan, Sarah; et al.
Abstract: Primary pulmonary histiocytic sarcoma (PHS) is a rare form of dendritic cell or macrophage neoplasia originating within the pulmonary parenchyma. There is limited literature describing prognosis in dogs with PHS receiving curative‐intent treatment consisting of surgical excision and adjuvant chemotherapy. The primary objective of this study was to report outcomes in dogs with localized PHS treated with standardized local and systemic therapy. A secondary objective was to identify prognostic factors in this population. A multi‐institutional retrospective study was performed and medical records including all surgical and histopathologic reports were retrospectively reviewed. For inclusion, dogs were required to have confirmed localized PHS and they must have undergone curative‐intent surgery with resection of all gross primary tumour and enlarged tracheobronchial lymph nodes; additionally, they must have received curative‐intent treatment with adjuvant single‐agent CCNU chemotherapy. Twenty‐seven dogs from six veterinary teaching hospitals and five private practices treated from 2008–2019 were included. The overall median survival time was 432 days. Higher CCNU dose was demonstrated to have a negative impact on survival on univariate, but not multivariable, analysis. Factors that were not found to be associated with survival on univariate analysis included body weight, breed, clinical signs at the time of diagnosis, hypoalbuminaemia, tumour size, lung lobe affected, lymph node metastasis, surgical margins and CCNU dose reductions. This study supports a favourable prognosis for dogs diagnosed with localized PHS treated with curative‐intent surgery in addition to adjuvant CCNU chemotherapy and suggests that multimodal treatment may be advisable to attempt to prolong survival.